2018
DOI: 10.1590/s0100-204x2018001100008
|View full text |Cite
|
Sign up to set email alerts
|

Viability of peach palm by-product, Spirulina platensis, and spinach for the enrichment of dehydrated soup

Abstract: The objective of this work was to develop dehydrated soup formulations using flour from peach palm by-product (PPB), Spirulina platensis or spinach, as well as to evaluate their composition by physical, chemical, instrumental, and sensory methods. Four formulations were developed: standard, PPB flour, PPB flour and S. platensis, and PPB flour and spinach. The samples were analyzed for proximate composition, chlorophyll content, total phenolic compounds, antioxidant activity, color, viscosity, water absorption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Microalgae are rich in high quality proteins, polyunsaturated fatty acids (PUFAs) including docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), and bioactive molecules with health promoting properties such as phycocyanin, lutein, or astaxanthin [3]. Due to the high content of nutrients and health-promoting compounds, microalgae have been evaluated in several scientific publications as innovative ingredients for the formulation of functional baked products [4,5], beverages [6,7], pasta [8,9], and other foodstuffs [10,11]. Although the number of microalgae containing food products launched into the market is increasing every year, microalgae products are not yet a common food ingredient, at least in Western cultures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae are rich in high quality proteins, polyunsaturated fatty acids (PUFAs) including docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), and bioactive molecules with health promoting properties such as phycocyanin, lutein, or astaxanthin [3]. Due to the high content of nutrients and health-promoting compounds, microalgae have been evaluated in several scientific publications as innovative ingredients for the formulation of functional baked products [4,5], beverages [6,7], pasta [8,9], and other foodstuffs [10,11]. Although the number of microalgae containing food products launched into the market is increasing every year, microalgae products are not yet a common food ingredient, at least in Western cultures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the improved nutritional value, the authors observed reduced sensory acceptability with increasing levels of microalgae formulation. In contrast to this study, Los et al [ 115 ] formulated a dehydrated soup with A. platensis at 15% ( w / w ), resulting in improved nutritional value (i.e., protein, fiber, chlorophyll, lipids and antioxidant capacity), with no compromise on acceptability when subjected to sensory evaluation. Based on these reports, there is a need for in-depth studies on formulation strategies that will enable effective microalgal food substitutions (i) for improved functionality and (ii) no/limited sacrifice of sensory quality.…”
Section: Microalgae Utilization For Food Formulationsmentioning
confidence: 71%
“…Regarding the low sensory acceptance, the authors highlight the need for further studies evaluating the amount of Spirulina that can be added to soups to improve the acceptance of formulations. Los et al (2018) Protein concentrate Spirulina platensis Spirulina proteins were extracted and concentrated to produce a protein concentrate. The green–blue concentrate showed 75.97 % of proteins and 19.44 % of carbohydrates (in dry mass).…”
Section: Spirulina : Functional Foods and Emerging Technologiesmentioning
confidence: 99%
“…Its application in food has proved to be quite interesting from a nutritional point of view. Some authors report an increase in the protein concentration of the formulated product after the addition of Spirulina ( Almeida et al, 2021 , da Silva et al, 2021b , Los et al, 2018 , Lucas et al, 2020 , Lucas et al, 2018 , de Oliveira et al, 2021 ). Moreover, by isolating and concentrating Spirulina proteins, Menegotto et al (2019) identified all essential amino acids in the concentrate.…”
Section: Spirulina : Functional Foods and Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation